2015
DOI: 10.1186/s13048-015-0200-0
|View full text |Cite|
|
Sign up to set email alerts
|

Ovarian stem cells are always accompanied by very small embryonic-like stem cells in adult mammalian ovary

Abstract: BackgroundExisting dogma that a female is born with fixed number of eggs was challenged by the detection of stem cells in adult mammalian ovary. Data has accumulated in support of ovarian stem cells (OSCs) proliferation, maintenance in culture, formation of germ cell nests and differentiation into oocytes and primordial follicle assembly using different strategies.ResultsFlow cytometry analysis identified >8 μm OSCs which are DDX1 positive and are considered equivalent to spermatogonial stem cells (SSCs) in te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 28 publications
1
34
0
Order By: Relevance
“…Adult mammalian ovaries not only acts as reservoirs for oocytes but also have the presence of other valuable stem cell sources such as OSCs and VSELs. Despite having smaller sizes than OSCs, VSELs express nuclear OCT4 rather than cytoplasmic OCT4 in OSCs, which defines their pluripotent nature [101]. These pluripotent cells can be isolated from a number of other adult cell sources such as bone marrow [102], bone [103], umbilical cord blood [104], and peripheral blood [105], and they can be used to derive OLCs when induced under suitable culturing conditions.…”
Section: Very Small Embryonic-like Stem Cells (Vsels): New Heroes In mentioning
confidence: 99%
“…Adult mammalian ovaries not only acts as reservoirs for oocytes but also have the presence of other valuable stem cell sources such as OSCs and VSELs. Despite having smaller sizes than OSCs, VSELs express nuclear OCT4 rather than cytoplasmic OCT4 in OSCs, which defines their pluripotent nature [101]. These pluripotent cells can be isolated from a number of other adult cell sources such as bone marrow [102], bone [103], umbilical cord blood [104], and peripheral blood [105], and they can be used to derive OLCs when induced under suitable culturing conditions.…”
Section: Very Small Embryonic-like Stem Cells (Vsels): New Heroes In mentioning
confidence: 99%
“…Cells will then gradually develop into adult cells, and the number of ES/progenitor cells is rapidly reduced, along with a decrease in potential differentiation activity. However, previous studies have suggested that embryonic-like stem cells, also called very small embryonic-like stem cells (VSELs), are present in various adult tissues, such as mammalian ovaries [3, 4], blood [5, 6], and umbilical cord blood [7, 8]. Additionally, some cells expressing ES cell-specific markers, such as Oct4, Nanog, and stage-specific embryonic antigen 4 (SSEA-4), have been identified in cord blood [9] and the adult pancreas [10].…”
Section: Introductionmentioning
confidence: 99%
“…The sperm generated in vitro were not tested further since we are apprehensive of sperm obtained in a dish from VSELs after 21 days culture for clinical use. We are more enthusiastic to restore spermatogenesis by endogenous manipulation of surviving stem cells in a nonfunctional, chemoablated gonad by injecting healthy niche cells (17) and allow Mother Nature to do the rest. Sperm collected from the caudal epithelium part of epididymis by this approach were able to fertilize eggs in vitro and initiate cleavage.…”
Section: Commentarymentioning
confidence: 99%
“…The VSELs exist in adult ovary (13)(14)(15) and testis (17)(18)(19)(20) in addition to the tissue specific progenitors including ovary stem cells (OSCs) in ovary and spermatogonial stem cells (SSCs) in testis. VSELs survive oncotherapy in both mice (15,18) and human (21) gonads because of their quiescent nature whereas OSCs/SSCs and germ cells get destroyed since oncotherapy basically targets actively dividing cells.…”
Section: Commentarymentioning
confidence: 99%